Domino Cyclization Initiated by Cross‐Rauhut–Currier Reactions. Issue 28 (26th June 2013) - Xie, Peizhong; Huang, You
Abstract: The Rauhut–Currier reaction has proved itself as a promising strategy for synthesis of multifunctionalized molecules, although still being in its infancy with regard to limitations of selectivity and scope. Considerable attention has thus been devoted to resolution of difficulties associated with controlling strategies and enantioselectivity. Carbocycles with distinct structural frameworks can be assembled rapidly through incorporation of cross‐Rauhut–Currier reactions into domino processes. The fine compatibility and widespread utility of Rauhut–Currier reactions is illustrated with several recent outstanding examples, with the aim of shedding light on the design of new substrates and catalysts for syntheses of complex molecules. Abstract : The Rauhut–Currier reaction is an efficient method for carbon‐carbon bond formation and displays fine compatibility, although still being in its infancy with regard to limitations of selectivity and scope. Structurally distinct carbocycle frameworks can be assembled rapidly through incorporation of cross‐Rauhut–Currier reactions into domino processes.